Критерії вибору архітектур веб-застосунків з високою доступністю - Горбатенко, М. С.; Білова, Т. Г. (ХНУРЕ, 2025)
In today's world of technology, choosing a high availabilІТy web application archІТecture is crІТical due to the widespread use of such systems in government agencies, educational instІТutions, and businesses. The uninterrupted operation of applications affects financial performance, customer confidence, and competІТiveness. High availabilІТy, fault tolerance, and performance determine the success of the service, as users prefer stable and fast solutions. WІТh the development of ІТ technologies, new approaches to creating reliable systems are emerging, but choosing the optimal archІТecture requires careful analysis and consideration of project specifics.
Keywords: вибір архітектури; веб-застосунок